Application of CRISPR/Cas System in the Metabolic Engineering of Small Molecules. - Singh, R.; Chandel, S.; Ghosh, A.; Dey, D.; Chakravarti, R.; Roy, S.; Ghosh, D.
Clustered regularly interspaced short palindromic repeats (CRISPR)and their associated Cas protein technology area is rapidly growing technique for genome editing and modulation of transcription of several microbes. Successful engineering in microbes requires an emphasis on the aspect of efficiency and targeted aiming, which can be employed using CRISPR/Cas system. Hence, this type of system is used to modify the genome of several microbes such as yeast and bacteria. In recent years, CRISPR/Cas systems have been chosen for metabolic engineering in microbes due to their specificity, orthogonality, and efficacy. Therefore, we need to review the scheme which was acquired for the execution of the CRISPR/Cas system for the modification and metabolic engineering in yeast and bacteria. In this review, we highlighted the application of the CRISPR/Cas system which has been used for the production of small molecules in the microbial system that is chemically and biologically important.
Keywords: CRISPR-CAS; METABOLIC ENGINEERING; SMALL MOLECULES